Sorry! : the classic game of sweet revenge [games]. (Hasbro Gaming, 2020)
Slide, collide and score to win the game of Sorry! Draw cards to see how far you get to move one of your pawns on the board. If you land on a Slide you can zip to the end and bump your opponent' pawns or your own! Jump over pawns and hide in your Safety zone while getting powers with the 2 power-up tokens. Keep on moving and bumping until you get all three of your pawns from your color Start to your color Home. But watch out, because if you get bumped, Sorry! It's all the way back to Start! --